The Effectiveness of Mediation as an Instrument for Land Dispute Resolution: A Normative Legal Study of the Role of the National Land Agency in Lamongan Regency - Galih Raka Dewa; Agus Supriyo (Faculty of Law, Muhammadiyah University of Surabaya, 2024)
The strategic socio-economic value of land in Indonesia often triggers complex disputes that are inefficiently resolved through litigation, necessitating mediation as a more equitable alternative. This study aims to evaluate the effectiveness of mediation in resolving land disputes, particularly in Lamongan Regency. The research method used is normative juridical. The results indicate that the effectiveness of mediation is significantly determined by a constellation of factors, including the parties' good faith, mediator competence, documentary completeness, and public legal literacy. However, findings reveal that mediation in Lamongan remains suboptimal due to several critical barriers. Specifically, the research identifies that low public legal awareness and the persistent egoism of disputing parties often lead to deadlocks during the negotiation process. Furthermore, the inability of mediators to employ effective communication techniques and psychological approaches frequently results in a failure to reach a formal peace agreement (Akta Perdamaian). Literature studies at the Lamongan Land Office (BPN) confirm that these internal and external constraints prevent mediation from becoming the primary choice for dispute resolution. Consequently, many cases that could be settled through non-litigation channels eventually escalate to court, increasing the burden on the judicial system. To enhance effectiveness, this study recommends intensive legal socialization to the community, specialized certification and training for professional mediators, and the institutional strengthening of the BPN’s role as a facilitator to ensure a more sustainable, fair, and legally certain dispute resolution framework in Indonesia.